Hubungan Kecerdasan Intelektual Dengan Prestasi Belajar Santri Dayah Terpadu Almadinatuddiniyah Syamsuddhuha Cot Murong Aceh Utara - Nurhayati AR; Syahrizal Syahrizal (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2016)
This research is aimed at acknowledging the relation between intellectual intelligence and learning achievement of the students in the Dayah Almadinatuddiniyah Syamsuddhuha, Cot Murong, North Aceh. The research was conducted for 6 months, from June to December 2014. This research is a descriptive research using correlational plan. Variables in this research are intellectual intelligence as predictor variable and learning achievement as criterion variable. The population of this research comprises all 2nd and 3rd grade junior high school students and 2nd and 3rd grade senior high school students of the Almadinatuddiniyah Syamsuddhuha Integrated Islamic Boarding School for the academic year of 2014/2015 with the total number of 305 students. The samples were taken from 20% (61 students) of the total population (305 students) using the stratified proportional random sampling method. For research hypothetical test, data were analyzed with the parametric inferential statistical technique by using the moment product correlation, simple regression, double regression and partial correlation techniques. The research results show that there is significant relation between the students’ intellectual intelligence and learning achievement. The students’ intellectual intelligent and learning achievement has correlation coefficient as much as 0.9765 and the effective contribution given by the intellectual intelligence variable to the students’ learning achievement is 95.69%.